Impact of Dorsal Root Ganglia Cryoextract on Histological Steatures in Dices and Contractility of Uterus in Differently Aged Rats - Nesteruk, Hanna; Ustichenko , Viktoriya; Alabedalkarim , Nataliya; Padalko , Volodymyr; Protsenko , Olena; Legach , Ievgen (Problems of Cryobiology and Cryomedicine, 2021)
To date, the number of women giving birth to their first child in late reproductive age is increasing around the world. This stipulates a need in designing the new approaches to restore the uterine contractile activity. In this paper, the histological features of uterus and its contractile activity have been experimentally studied in differently aged rats after the dorsal root ganglia cryoextract (DRGCE) administration. The cryoextract was derived from dorsal root ganglia of neonatal piglets by three-fold freezing down to –196°C in saline, followed by thawing at room temperature, homogenization and centrifugation. Here, we used the female rats of reproductive age (RA, 6-month-old) and those of late reproductive age (LRA, 14-month-old). Animals of both age groups received intraperitoneally either DRGCE (experimental groups) or saline (control groups) for 9 days by 0.2 ml. To days 28–29 after administration beginning the animals were sacrificed and the uterine fragments were taken for histological examination and study of oxytocin (OT)-induced uterine contractile activity (UCA). The strength of OT-induced uterine isometric contraction was found to decrease by 28.6% in LRA rats vs. the RA ones. The DRGCE administration to LRA rats increased the UCA indices, namely the contractile frequency, contractile amplitude and strength of isometric contraction augmented by 25, 9.8 and 30% respectively, as compared with the group of the same age without DRGCE introduction. This effect was observed on the background normal uterine histological structure and unchanged myometrial thickness. Probl Cryobiol Cryomed 2021; 31(3): 258–267